Design and development of unstuck tourniquet - Alifurochmah, Isty; Endiyono, Endiyono (Universitas Muhammadiyah Purwokerto, 2023)
Background: Existing tourniquets often get stuck, so innovation is needed to develop unstuck tourniquets.Technic: The result of the development of the tourniquet is only to modify the location of the locking system. The locks are located on the right and left sides, with an internal locking system that uses a bent angle design, which functions as a spring force to push the lockout without obstacles. The outside of the locking system has nuts and bolts that hold the cuff tighter when used.Conclusion: The results of the development of this tourniquet are proven easy to use, comfortable, and unstuck.